2001
DOI: 10.1128/mcb.21.20.6731-6737.2001
|View full text |Cite
|
Sign up to set email alerts
|

cis Recognition Elements in Plant Mitochondrion RNA Editing

Abstract: RNA editing in higher plant mitochondria modifies mRNA sequences by means of C-to-U conversions at highly specific sites. To determine the cis elements involved in recognition of an editing site in plant mitochondria, deletion and site-directed mutation constructs containing the cognate cox II mitochondrial gene were introduced into purified mitochondria by electroporation. The RNA editing status was analyzed for precursor and spliced transcripts from the test construct. We found that only a restricted number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 38 publications
4
75
0
1
Order By: Relevance
“…7). Such comparisons suggested that upstream (5Ј) sequences are crucial in targeting the editing machinery and that downstream similarities are not sufficient to specify a site.These observations were corroborated by the recent breakthrough development of an in vitro editing system for plastids (8, 9) and an electroporation protocol for mitochondria (10,11). Mutational analysis of templates in these as well as in in vivo experiments in transgenic chloroplasts (12)(13)(14) showed that for several editing sites 20 -30 nucleotides upstream and 2-5 nucleotides downstream are sufficient to guide the editing activity, precisely what had initially been deduced for mitochondria (7).…”
supporting
confidence: 55%
“…7). Such comparisons suggested that upstream (5Ј) sequences are crucial in targeting the editing machinery and that downstream similarities are not sufficient to specify a site.These observations were corroborated by the recent breakthrough development of an in vitro editing system for plastids (8, 9) and an electroporation protocol for mitochondria (10,11). Mutational analysis of templates in these as well as in in vivo experiments in transgenic chloroplasts (12)(13)(14) showed that for several editing sites 20 -30 nucleotides upstream and 2-5 nucleotides downstream are sufficient to guide the editing activity, precisely what had initially been deduced for mitochondria (7).…”
supporting
confidence: 55%
“…Consistent with these observations, conversion to G abolished both psbE and petB mRNA editing in vitro. Similarly, the conversion of 5Ј neighboring residues to G in chloroplast ndhB (site V) mRNA and mitochondrial cox II (C259) mRNA were reported to inhibit editing in vivo (13,24). A guanosine at the 5Ј neighboring position is inhibitory for most editing sites studied; therefore, the strong bias against G may be due to mechanical constraints.…”
Section: Discussionmentioning
confidence: 99%
“…The development of reliable in vitro RNA editing activities for chloroplasts [7][8][9] and mitochondria [10,11] as well as in organello editing [12][13][14][15] in the past few years, has accelerated progress towards elucidating the cis-requirements. For plant mitochondria, in vitro RNA editing in pea lysates and in organello editing in wheat show that for some editing events only about 15-30 nucleotides are necessary upstream and very few or none downstream.…”
Section: Introductionmentioning
confidence: 99%